2010
DOI: 10.1007/s11947-010-0409-2
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Kinetics of Colour and Total Carotenoids in Jackfruit (Artocarpus heterophyllus) Bulb Slices During Hot Air Drying

Abstract: The kinetics of colour and carotenoids degradation in jackfruit bulb slices was evaluated during hot air drying at 50, 60 and 70°C. Visual colour as well as total carotenoids (TC) content was found to be influenced by the drying process. Tri-stimulus colour parameters such as Hunter L and b values decreased and a value increased during drying. The combination of Hunter L×b value was found to represent the colour change adequately. Degradation of TC and visual colour in terms of Hunter L×b value followed first-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
49
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 34 publications
9
49
0
4
Order By: Relevance
“…Correlations between visual colour coordinates with carotenoids content have been widely discussed in the literature. Saxena et al [17] found that the degradation of colour parameters Hunter L*×b* value and the total carotenoids of jackfruit bulb slices agreed well with the first-order reaction kinetics during hot air drying. Moreover, there was a certain correlation between total carotenoids and the L*×b* value, and the combination of Hunter L*×b* value could replace carotenoid content for online quality control adequately.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…Correlations between visual colour coordinates with carotenoids content have been widely discussed in the literature. Saxena et al [17] found that the degradation of colour parameters Hunter L*×b* value and the total carotenoids of jackfruit bulb slices agreed well with the first-order reaction kinetics during hot air drying. Moreover, there was a certain correlation between total carotenoids and the L*×b* value, and the combination of Hunter L*×b* value could replace carotenoid content for online quality control adequately.…”
Section: Introductionmentioning
confidence: 78%
“…However, Ahmed et al [39] observed that apart from the Hunter b* value, both L* and a* values also decreased with time at a given temperature as the mango puree turned brown. Chutintrasri and Noomhorm [40] and Saxena et al [17] both found that the Hunter L* and b* values decreased and the a* value increased during heat-treated pineapple puree at 70-110 º C and hot-air drying for jackfruit bulb slices. The different results may be due to the changes in the yellow and red colour of the pumpkin slices, which may be caused not only by the variation of carotenoids content but also by a series of complex Maillard reactions in the drying process.…”
Section: Degradation Kinetics Of β-Carotenementioning
confidence: 97%
See 3 more Smart Citations